Alzheimer’s Disease Enhanced Tonic Inhibition is Correlated With Upregulated Astrocyte GABA Transporter-3/4 in a Knock-In APP Mouse Model - Aldabbagh, Yousif; Islam, Anam; Zhang, Weicong; Whiting, Paul; Ali, Afia B. (Frontiers in Pharmacology, 2022)
Cognitive decline is a major symptom in Alzheimer’s disease (AD), which is strongly associated with synaptic excitatory-inhibitory imbalance. Here, we investigated whether astrocyte-specific GABA transporter 3/4 (GAT3/4) is altered in APP knock-in mouse model of AD and whether this is correlated with changes in principal cell excitability. Using the APPNL-F/NL-F knock-in mouse model of AD, aged-matched to wild-type mice, we performed in vitro electrophysiological whole-cell recordings combined with immunohistochemistry in the CA1 and dentate gyrus (DG) regions of the hippocampus. We observed a higher expression of GAD67, an enzyme that catalyses GABA production, and GAT3/4 in reactive astrocytes labelled with GFAP, which correlated with an enhanced tonic inhibition in the CA1 and DG of 12–16-month-old APPNL-F/NL-F mice compared to the age-matched wild-type animals. Comparative neuroanatomy experiments performed using post-mortem brain tissue from human AD patients, age-matched to healthy controls, mirrored the results obtained using mice tissue. Blocking GAT3/4 associated tonic inhibition recorded in CA1 and DG principal cells resulted in an increased membrane input resistance, enhanced firing frequency and synaptic excitation in both wild-type and APPNL-F/NL-F mice. These effects exacerbated synaptic hyperactivity reported previously in the APPNL-F/NL-F mice model. Our data suggest that an alteration in astrocyte GABA homeostasis is correlated with increased tonic inhibition in the hippocampus, which probably plays an important compensatory role in restoring AD-associated synaptic hyperactivity. Therefore, reducing tonic inhibition through GAT3/4 may not be a good therapeutic strategy for AD.